Endothelial nitric oxide synthase single nucleotide polymorphism and left ventricular function in early chronic kidney disease. - Sourabh Chand; Colin D Chue; Nicola C Edwards; James Hodson; Matthew J Simmonds; Alexander Hamilton; Stephen C L Gough; Lorraine Harper; Rick P Steeds; Jonathan N Townend; Charles J Ferro; Richard Borrows (PLoS ONE)
Background Chronic kidney disease (CKD) is associated with accelerated cardiovascular disease and heart failure. Endothelial nitric oxide synthase (eNOS) Glu298Asp single nucleotide polymorphism (SNP) genotype has been associated with a worse phenotype amongst patients with established heart failure and in patients with progression of their renal disease. The association of a cardiac functional difference in non-dialysis CKD patients with no known previous heart failure, and eNOS gene variant is investigated. Methods 140 non-dialysis CKD patients, who had cardiac magnetic resonance (CMR) imaging and tissue doppler echocardiography as part of two clinical trials, were genotyped for eNOS Glu298Asp SNP retrospectively. Results The median estimated glomerular filtration rate (eGFR) was 50 mls/min and left ventricular ejection fraction (LVEF) was 74% with no overt diastolic dysfunction in this cohort. There were significant differences in LVEF across eNOS genotypes with GG genotype being associated with a worse LVEF compared to other genotypes (LVEF: GG 71%, TG 76%, TT 73%, p = 0.006). After multivariate analysis, (adjusting for age, eGFR, baseline mean arterial pressure, contemporary CMR heart rate, total cholesterol, high sensitive C-reactive protein, body mass index and gender) GG genotype was associated with a worse LVEF, and increased LV end-diastolic and systolic index (p = 0.004, 0.049 and 0.009 respectively). Conclusions eNOS Glu298Asp rs1799983 polymorphism in CKD patients is associated with relevant sub-clinical cardiac remodelling as detected by CMR. This gene variant may therefore represent an important genetic biomarker, and possibly highlight pathways for intervention, in these patients who are at particular risk of worsening cardiac disease as their renal dysfunction progresses.